A single-cell multi-omics atlas of rice - Wang, Xiangyu; Huang, Huanwei; Jiang, Sanjie; Kang, Jingmin; Li, Dongwei; Wang, Kailai; Xie, Shang; Tong, Cheng; Liu, Chaofan; Hu, Guihua; Li, Haoqian; Li, Cong; et al. (Nature, 2025)
Cell functions across eukaryotes are driven by specific gene expression programs, which are dependent on chromatin structure1-3. Here we report a single-cell multi-omics atlas of rice, one of the world’s major crops. By simultaneously profiling chromatin accessibility and RNA expression in 116,564 cells from eight organs, we identified cell-type-specific gene regulatory networks and described novel cell states, such as a ‘transitional state’ in floral meristems. On the basis of our network analyses, we uncovered the function of the cell-type-specific regulatory hubs RSR1, F3H and LTPL120 during rice development. Our analysis revealed correlations between cell type and agronomic traits, as well as conserved and divergent cell-type functions during evolution. In summary, this study not only offers a unique single-cell multi-omics resource for a major crop but also advances our understanding of cell-type functions and the underlying molecular programs in rice.